Sound source localization for subband-based two speech separation in room environment - Dam, H.; Nordholm, Sven (IEEE, 2013)
This paper investigates the problem of subband speech separation from a mixture of two speech signals in a room environment. Due to the lack of source information, a sound source localization is proposed for beamformer design in each subband to obtain a good interference suppression with negligible expense on each target signal integrity. Evaluations on real speech data show that the proposed speech separation method offers a good interference suppression level whilst maintaining a low distortion level of the target source.